PID Control System for Shaking Table and Bearing Capacity Measurement on Soil Liquefaction Simulator - Setiowati, Sulis; Sanubari, Agung; Nuraulia Rahmah, Firly; Salimah, A'isyah; Yelvi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Liquefaction occurs when soil that was previously stable and solid suddenly loses its strength and stiffness within a short period. This research develops a model for testing soil liquefaction using a 1-g shaking table. The system, based on LabVIEW, is designed to measure and analyze the performance of foundations during soil liquefaction tests. It enables the evaluation of soil characteristics before, during, and after an earthquake that could induce liquefaction, while also considering foundation reinforcement. In this study, the Ziegler-Nichols PID tuning method was employed to improve control accuracy and stability during seismic vibration simulations and to measure soil bearing capacity. The results indicate that the system achieved a rise time of 8 seconds, a delay time of 13 seconds, an overshoot of 0.06%, a settling time of 13 seconds, and a steady-state error of 0.02%. Compared to the Trial Error method, the Ziegler-Nichols method achieves faster rise time, delay time, and settling time but results in higher overshoot and steady-state error. The sensor data provides detailed information about the helical pile's ability to support vertical loads, with an average bearing capacity of 3.99 kPa.